Emissões de gases de efeito estufa (GEE) nos municipios do estado do Pará: uma investigação sobre a dinamica e políticas de mitigação no periodo 2000 a 2020 - Nogueira, Fernando (2023)
This dissertation analyzes the dynamics of the evolution of GHG emissions in each integration region (IR) of the state of Pará, and how these emissions relate to the predominant activities in the municipalities of the state during the period from 2000 to 2020. The central objective is to examine whether, according to the economic dynamics of this territory, it is possible for the municipalities of Pará to adopt effective environmental public policies at the local level with the capacity to contribute effectively to the reduction/mitigation of Greenhouse Gas Emissions (GHG) in the Legal Amazon. The research results show a concentration of GHG emissions located in the regions of agricultural and livestock frontier expansion, and even though the municipalities have a well-established institutional framework and are already using many tools for environmental management, they lack the support of other levels of government (state and federal) to contain deforestation resulting from economic activities involving land and forest transformation. This condition exceeds the capacity of the municipalities to act in command and control and oversight actions. Throughout this period, the municipalities that emitted the most in the state have a extensive history of deforestation and are concentrated in regions that maintained their economic activities linked to agriculture and livestock. It is also observed, through the analysis of the carbon intensity indicator (CI), that there is a process of decarbonization of the economy of the Pará municipalities, motivated by the closure of economic cycles linked to deforestation. However, the volume of GHG emissions in the Pará municipalities compromises the fulfillment of the goals established by Brazil in the Paris Agreement.